2005
DOI: 10.1074/jbc.m411787200
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-18 Is a Pro-hypertrophic Cytokine That Acts through a Phosphatidylinositol 3-Kinase-Phosphoinositide-dependent Kinase-1-Akt-GATA4 Signaling Pathway in Cardiomyocytes

Abstract: In patients with congestive heart failure, high serum levels of the proinflammatory cytokine interleukin (IL)-18 were reported. A positive correlation was described between serum IL-18 levels and the disease severity. IL-18 has also been shown to induce atrial natriuretic factor (ANF) gene expression in adult cardiomyocytes. Because re-expression of the fetal gene ANF is mostly associated with hypertrophy, a hallmark of heart failure, we hypothesized that IL-18 induces cardiomyocyte hypertrophy. Treatment of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 75 publications
(57 reference statements)
6
114
1
2
Order By: Relevance
“…23) p21 has a wide specificity for substrates such as CDK4/6, CDK2, and Cdc2, leading to cell cycle arrest at multiple phases. 22 27,[32][33][34] Because ANP gene expression is mediated by the transcription factor GATA-4 and signaling pathways leading to cardiomyocyte hypertrophy activate GATA-4 under various hypertrophic conditions, 35,36) upregulation of ANP gene expression suggests activation of a signaling pathway leading to the development of hypertrophy. It is possible that H 2 O 2 activated the hypertrophic signaling pathway in H9c2 cells even in the presence of BAPTA-AM.…”
Section: Discussionmentioning
confidence: 99%
“…23) p21 has a wide specificity for substrates such as CDK4/6, CDK2, and Cdc2, leading to cell cycle arrest at multiple phases. 22 27,[32][33][34] Because ANP gene expression is mediated by the transcription factor GATA-4 and signaling pathways leading to cardiomyocyte hypertrophy activate GATA-4 under various hypertrophic conditions, 35,36) upregulation of ANP gene expression suggests activation of a signaling pathway leading to the development of hypertrophy. It is possible that H 2 O 2 activated the hypertrophic signaling pathway in H9c2 cells even in the presence of BAPTA-AM.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoretic mobility shift (EMSA), ELISA, reporter assays NF-κB DNA-binding activity in nuclear protein extracts was analyzed by EMSA [9][10][11][12]. The following double-stranded oligonucleotides were used: consensus, 5′-AGTTGAGGGGACTTTCCCAGGC-3′; mutant, 5′-AGTTGAGGCGACTTTCCCAGGC-3′ (Santa Cruz Biotechnology, Santa Cruz, CA).…”
Section: Adenoviral Transductionmentioning
confidence: 99%
“…Isolation of whole cell homogenates, electrophoresis, electroblotting, and Western blotting using the ECL chemiluminescence detection system were previously described [9][10][11][12]. Mitochondrial and cytoplasmic fractions were prepared using the Mitochondrial Fractionation Kit (Active Motif).…”
Section: Protein Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…4,21 In addition, ANP, a cardiac hypertrophy marker, is activated in an Akt-dependent manner. 22 However, one study reported that short-term activation of Akt-induced cardiac hypertrophy without ANP gene expression. 23 Moreover, ERK is considered to be activated by mechanical stress, which induces a G-protein-coupled hypertrophic stimulation in heart failure.…”
Section: Cardioprotection By Kallistatin Via Antioxidation L Gao Et Almentioning
confidence: 99%